Облік витрат у рекламних кампаніях - Голуб, Наталя Олександрівна; Holub, Nataliia (Вісник Одеського національного університету, 2023)
UA: У статті досліджено види реклами, її значення в сучасному суспільстві та для підприємства зокрема Визначено, що витрати на рекламу є необхідними у діяльності підприємств. Правильна реклама може змусити не тільки переконаніше підприємство себе чути, а й освоювати нові перспективні ринки. Розглянуто форму та оподаткування витрат на рекламу та маркетингові витрати. Визначено особливості не вивчення нематеріальними активами, об'єкти інтелектуальної власності, а вивчення витрат звітного періоду та включення їх до витрат на збут. Зведено складені витрати на рекламу та маркетингові витрати. Проаналізовано методи формування витрат на рекламу при оформленні договору про надання послуг. Обґрунтовано організаційні та методичні аспекти щодо форми витрат на рекламу та маркетингових витрат у сучасних умовах. EN: The article examines the types of advertising, its importance in modern society and for the enterprise in particular. In modern conditions, any successful business needs advertising, because advertising is the driving force of trade and the main tool for promoting goods on the market. The procedure for documentary confirmation and disclosure of methodological principles of accounting and taxation of advertising costs in advertising campaigns is considered. It was determined that advertising expenses are necessary in the activities of enterprises. Advertising costs can reach significant levels. Correct advertising can make not only the company feel more confident, but also develop new promising markets. Considered how to account for and tax such expenses. The need to recognize intangible assets in the form of intellectual property objects arising in the course of the advertising process has been determined. In the accounting of sales costs, it is considered a mistake: to include advertising services in the cost of the product being produced (advertising can be a temporary phenomenon and it is not related to the production, namely to the sale of the product) and to recognize intangible assets (costs for advertising and promotion products on the market are not recognized as intangible assets). The components of advertising and marketing costs have been clarified. It should be noted that the terms defining advertising costs and sales costs are used interchangeably in economic literature and in business practice. The drafting of the contractual relationship between the supplier and the buyer and the formation of costs in terms of tax consequences and risks during taxation are analyzed. It was found that the cost accounting will differ depending on how the contract was concluded with one or another company. To reduce tax risks, you should take care of proper documentation of the result of providing advertising services. It should be a contract for the provision of advertising services and an act of provision of advertising services. The organizational and methodical aspects of accounting for advertising and marketing costs in modern conditions are substantiated.
Cost accounting in advertising campaigns
Keywords: реклама; витрати; витрати на збут; маркетингові послуги; рекламна кампанія; рекламна дільність; товар; послуги; advertising; costs; sales costs; marketing services; advertising campaign; advertising activity; goods; services